A Contrast Adjustment Thresholding Method for Surface Defect Detection Based on Mesoscopy - Win, M.; Bushroa, A.R.; Hassan, M.A.; Hilman, N.M.; Ide-Ektessabi, A. (Institute of Electrical and Electronics Engineers (IEEE), 2015)
Titanium-coated surfaces are prone to tiny defects such as very small cracks, which are not easily observable by the naked eye or optical microscopy. In this study, two new thresholding methods, namely contrast-adjusted Otsu's method and contrast-adjusted median-based Otsu's method, are proposed for automated defect detection system for titanium-coated aluminum surfaces. The two proposed methods were compared with four existing thresholding techniques in terms of accuracy and speed of defect detections for images of 700, 900, and 1000 dpi obtained using high-resolution scanning. Experimental results have shown that the proposed contrast-adjusting methods have performance similar to minimum error thresholding (MET) and are generally better than Otsu's method.